Analisis Pengaruh Promosi, Kualitas Pelayanan, Produk, dan Religiusitas Terhadap Minat Nasabah Membeli Produk Asuransi Syariah (Studi Pada PT Sun Life Syariah Cabang Padang) - Fanny Oktivia Denovis; Yurniati Yurniati; Januarius Januarius; Nailul Yuni Permataputri (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
The sharia insurance industry in Indonesia has grown rapidly, yet the number of customers at the branch level, such as at PT Sun Life Syariah Padang Branch, remains fluctuating and has not reached its optimal potential. This study aims to analyze the effect of promotion, service quality, product, and religiosity on customer interest in purchasing sharia insurance products at the company. A quantitative correlational approach was applied, involving 30 customers as the sample obtained through accidental sampling. Data were collected using a Likert-scale questionnaire and processed through validity tests, reliability tests, classical assumption tests, and multiple linear regression with the aid of SPSS 27. The results show that partially, all four variables have a positive but not significant effect on customer interest, with promotion contributing the largest relative influence (regression coefficient 0.287; beta 0.347). Simultaneously, promotion, service quality, product, and religiosity significantly affect customer interest (F count 5.932 > F table 2.76; significance 0.002), with the model explaining 48.7% of the variation in customer interest (R = 0.698; R² = 0.487), while the remaining 51.3% is explained by other factors outside the model. These findings indicate that a marketing strategy combining attractive promotion with responsive service is the most relevant step to increase public interest in sharia insurance products.